Application of Natural Deep Eutectic Solvents (NADES) in the Natural Product of Antioxidant Activity - Hidayah, Andi Nurul Annisa; Ahmad, Aktsar Roskiana; Rasyid, Faradiba Abdul (Poltekkes Kemenkes Gorontalo, 2025)
The extraction of bioactive compounds from plant-based materials poses significant challenges due to the limitations of traditional organic solvents, including toxicity and environmental impact. Natural Deep Eutectic Solvents (NADES), formed from natural components at defined molar ratios, have emerged as green, sustainable alternatives for efficient extraction. This literature review aims to investigate the applications, compositions, and effectiveness of NADES in extracting antioxidant-rich compounds from natural sources. Relevant peer-reviewed articles published within the last ten years were retrieved from Google Scholar and PubMed using keywords such as “NADES,” “natural product,” and “antioxidant activity.” Studies included using NADES to extract phytochemicals, pharmaceuticals, or food compounds and address their toxicity, safety, and physicochemical properties. Non-peer-reviewed articles, unrelated solvent systems, and duplicate studies were excluded. The review identified compelling NADES compositions, including choline chloride: lactic acid (1:2), choline chloride: oxalic acid (1:1), and citric acid: glycerol (1:1), which demonstrated high extraction efficiency and antioxidant activity. The tunability of hydrogen bond donor and acceptor ratios allows NADES to be optimized for specific bioactive compounds. In conclusion, NADES offers a promising and eco-friendly approach for future applications in natural product extraction.